Use of progestogel in diffuse forms of mastopathy - E. V. Meskikh; N. I. Rozhkova (Опухоли женской репродуктивной системы)
The paper describes the diffuse forms of mastopathy and considers its symptoms and pathogenesis. It evaluates the efficacy of progestogel in the treatment of diffuse forms of mastopathy.